HUBUNGAN PEMBELAJARAN GERAKAN DASAR SENAM RITMIK DENGAN KEBUGARAN JASMANI SISWA SMP ISLAM AL MUMTAAZ - Ridho Saputra Alyan; Rekha Ratri Julianti; Dikdik Fauzi Dermawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between learning basic rhythmic gymnastics movements and physical fitness of students at Al Mumtaaz Islamic Middle School. Rhythmic gymnastics is a physical activity that combines body movements with musical rhythms systematically so that it can help improve students' coordination, balance, agility, endurance, and strength. However, the implementation of rhythmic gymnastics learning in schools is still not optimal due to the lack of variety in learning methods and low student interest in participating in learning activities, thus impacting students' physical fitness levels. This study uses a quantitative approach with a correlational method to determine the relationship between the variables of learning basic rhythmic gymnastics movements (X) and physical fitness (Y). The study population was 23 students of Al Mumtaaz Islamic Middle School in the 2025/2026 academic year with a sampling technique using total sampling. The research instruments were observation sheets to assess the ability of basic rhythmic gymnastics movements and physical fitness tests to measure students' physical condition. The data analysis technique used Pearson Product Moment correlation. The results of the study showed a significant relationship between learning basic rhythmic gymnastics movements and students' physical fitness. Students with good physical fitness tend to perform rhythmic gymnastics movements better, characterized by precise technique, coordination, balance, rhythmic alignment, and continuity. This research is expected to serve as a reference for physical education teachers in developing more effective and engaging rhythmic gymnastics lessons.